2013
DOI: 10.2754/avb201382040387
|View full text |Cite
|
Sign up to set email alerts
|

Canine gastrointestinal tract tumours: a restrospective study of 74 cases

Abstract: The aim of our study was to investigate histopathologically the incidence of gastrointestinal tract tumours in dogs in the Czech Republic in relation to their age, sex and breed. In total, 29 gastric and 45 intestinal tumours from 3827 gastrointestinal tract biopsies were investigated. The average age of dogs with gastric lymphoma, adenocarcinoma, and other mesenchymal tumours was 7.3 years, 9.5 years, and > 10 years, respectively. Breed predisposition to adenocarcinoma was evidenced in the Belgian Shepherd an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 10 publications
2
26
0
12
Order By: Relevance
“…2E) The present study, we reviewed 131 canine gastrointestinal epithelial tumors. While, information on the average age, location of tumor lesions, or predisposition towards a particular gender is already well-established [15][16][17] , the present study revealed that in Japan, gastrointestinal epithelial tumors occur more frequently in Jack Russell Terriers and Miniature Dachshunds. Previous reports on the subject revealed diverse results, with some authors stating that there was no predisposition towards any particular breed, in canine gastric neoplasms 15,18 , whereas others showed that Belgian Shepherd Dogs 19 , Collies 15 , German Shepherds 15,20 and West Highland White terriers 20 have increased risks of gastric or intestinal carcinoma.…”
Section: Histopathological Classification Of Intestinal Tumorsmentioning
confidence: 43%
“…2E) The present study, we reviewed 131 canine gastrointestinal epithelial tumors. While, information on the average age, location of tumor lesions, or predisposition towards a particular gender is already well-established [15][16][17] , the present study revealed that in Japan, gastrointestinal epithelial tumors occur more frequently in Jack Russell Terriers and Miniature Dachshunds. Previous reports on the subject revealed diverse results, with some authors stating that there was no predisposition towards any particular breed, in canine gastric neoplasms 15,18 , whereas others showed that Belgian Shepherd Dogs 19 , Collies 15 , German Shepherds 15,20 and West Highland White terriers 20 have increased risks of gastric or intestinal carcinoma.…”
Section: Histopathological Classification Of Intestinal Tumorsmentioning
confidence: 43%
“…Adenocarcinoma is one of the most common intestinal neoplasms in dogs, and comprises 20% to 53% of intestinal tumors, and 37 to 55% of intestinal malignancies (14,27). It carries a poor prognosis, and due to lack of specific clinical signs and late diagnosis, evidence of nodal or angiolymphatic invasion is noted in 52% and visceral metastases in 38% of cases at the time of diagnosis (25).…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal adenocarcinoma is one of the most common malignant tumors in canine gastrointestinal tract, together with lymphoma and sarcomas (leiomyosarcomas and gastrointestinal stromal tumors) (14,27). It presents generally with a high level of intestinal wall infiltration at the time of diagnosis, often with lymph node metastases, rendering a poor prognosis to the condition (25).…”
Section: Introductionmentioning
confidence: 99%
“…While most alimentary lymphomas are restricted to the gastrointestinal tract, one-third occur concomitantly with the multicentric form (Couto and others 1989, Rassnick and others 2009). Median age of affected dogs ranges between 8.2 and 10 years (Frank and others 2007, Rassnick and others 2009, Frgelecova and others 2013). …”
Section: Introductionmentioning
confidence: 99%